تمثلات الطلبة الجامعيين للمقاولاتية من خلال التكوين الجامعي - بالراشد, نبيل; جابر, مليكة (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الورقة البحثية إلى معرفة مساهمة التعليم المقاولاتي في تشكيل تمثلات الطلبة -المقبلين على التخرج -للمقاولاتية .من أجل ذلك إختار الباحث عينة طبقية مشكلة من 204طالب (مستوى ماستر)، موزعين على أربعة كليات بجامعة محمد خيضر ببسكرة ،مستخدما في ذلك أداة الإستبيان موجه للطلبة، والمقابلة كأداة ثانوية مع الأساتذة .ليخلص الباحث أن التعليم المقاولاتي في جامعة محمد خيضر ببسكرة لا يسهم في تشكيل تمثلات الطلبة-المقبلين على التخرج -للمقاولاتية إلا في بعض التخصصات الأكاديمية. Abstract: This research paper aims to know the contribution of entrepreneurial education in shaping the representations of students - who are about to graduate - for entrepreneurship. The questionnaire is directed to students, and the interview as a secondary tool with professors. The researcher concludes that entrepreneurship education at Mohamed Khider University of Biskra does not contribute to the formation of student representations - who are about to graduate - for entrepreneurship, except in some academic disciplines.
مقال
Keywords: تعليم ; تعليم مقاولاتي ; تمثلات ; مقاولاتية; education; entrepreneurial education; representations; Contracting